A new genus of Trachelipodidae Strouhal, 1953 (Crustacea, Isopoda, Oniscidea) from the eastern Mediterranean - Cardoso, Giovanna Monticelli; Taiti, Stefano; Sfenthourakis, Spyros (Zootaxa, 2015)
Levantoniscus n. gen. is erected for two new species from Cyprus: Levantoniscus bicostulatus n. sp. and Levantoniscus makrisi n. sp. Levantoniscus wahrmani (Strouhal, 1968) n. comb. from Israel and southern Turkey is transferred from the genus Bathytropa Budde-Lund, 1885 and family Bathytropidae. The new genus is included in the family Trachelipodidae and is characterized by distinct dorsal ornamentation, interlocking pleopods and uncovered pleopodal lungs which are located in invaginations on pleopod 3–5 exopodites.